2003
DOI: 10.1038/sj.onc.1206818
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-E is a strong predictor of endocrine therapy failure in human breast cancer

Abstract: Recently, cyclin-E was reported to be the most prominent prognostic factor for breast cancer outcome described so far, even surpassing axillary nodal involvement. Earlier studies on the prognostic value of cyclin-E in breast cancer, however, yielded heterogeneous results. Therefore, we set out to confirm and extend these results by quantitative Taqman RT-PCR of cyclin-E levels in 277 resectable breast cancers. Cyclin-E levels were not associated with relapse-free survival (RFS) or overall survival (OS) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 24 publications
6
57
1
Order By: Relevance
“…5,[24][25][26][27] We showed that CCNE1 and CCNE2 were both associated with RFI in a univariate analysis, whereas CCNE2 was the only significant variable in the multivariate model. However, when CCNE2 was discarded, CCNE1 became significant.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…5,[24][25][26][27] We showed that CCNE1 and CCNE2 were both associated with RFI in a univariate analysis, whereas CCNE2 was the only significant variable in the multivariate model. However, when CCNE2 was discarded, CCNE1 became significant.…”
Section: Discussionmentioning
confidence: 70%
“…The histological grade, as well as the ER status was significantly associated with clinical outcome in univariate analysis. All these variables were further compared in a multivariate model with backward stepwise selection based on hypotheses tests using likelihood ratios, starting only with the variables that had a As several studies reported CCNE and NE as markers predicting endocrine therapy failure, 5,9 we conducted a subgroup analysis in the 110 ER-positive tumors from patients treated with adjuvant tamoxifen only. The results regarding NE, PR3, CCNE1 and CCNE2 were visualized as Kaplan-Meier curves in Figure 2.…”
Section: Ne Pr3 Ccne1 and Ccne2 Expression Levels And Patient Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expression of cyclins is linked to breast cancer development and progression (Bindels et al, 2002;Akli et al, 2004;Caldon et al, 2006). While cyclin D1 overexpression is generally associated with an ERapositive phenotype and favorable clinical outcome, deregulation of cyclin E and A is linked to induction of centrosome amplification, aneuploidy, loss of ERa and poor outcome (Bindels et al, 2002;Span et al, 2003;Joe et al, 2005). One mechanism for preservation of genomic stability is through p53-mediated control of centrosome homeostasis (Fukasawa, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from Keyomarsi et al (75) argues convincingly that cyclin E expression levels are the single most powerful clinical parameter in predicting long term prognosis in breast cancer patients, with high levels of cyclin E having an even higher hazard ratio than the classic prognostic indicators cyclins D1 and D3, HER-2/neu, estrogen/progesterone receptor status, and lymph node metastases (75). Supplementing that argument, Span et al (76) recently reported that the expression level of cyclin E is a strong predictor of endocrine therapy failure in breast cancer patients, a result that builds upon mounting that evidence that cyclin E is a critical target of endocrine signaling in promoting steroid hormone-dependent tumor growth (77). Finally, 10 percent of mice that express a human cyclin E transgene develop carcinoma (78), and cyclin E knockout MEFs are strikingly resistant to transformation with oncogenic Ras (Ref.…”
Section: Rbmentioning
confidence: 99%